2023
DOI: 10.1259/dmfr.20220220
|View full text |Cite
|
Sign up to set email alerts
|

A miniaturized ultrasound transducer for monitoring full-mouth oral health: a preliminary study

Abstract: Objective: To customize a miniaturized ultrasound transducer to access full-mouth B-mode, color Doppler and spectral Doppler imaging for monitoring oral health. Methods: A customized periodontal ultrasound transducer SS-19–128 (19 MHz, 128 channels) 1.8 cm wide and 1 cm thick was developed and connected to a data acquisition (DAQ) system. B-mode, color Doppler, and spectral Doppler data could all be collected with SS-19–128. The imaging resolution and penetration capacity of SS-19–128 were characterized on pha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Fifteen included studies analyzed periodontal tissues with B-mode imaging around natural teeth, [31][32][33][40][41][42][43][44][45][46][47][48][49][50][51] 4 studies used US around implants, 32,52-54 2 studies investigated edentulous areas, 55,56 and 4 of them used color flow imaging. 36,[57][58][59]…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Fifteen included studies analyzed periodontal tissues with B-mode imaging around natural teeth, [31][32][33][40][41][42][43][44][45][46][47][48][49][50][51] 4 studies used US around implants, 32,52-54 2 studies investigated edentulous areas, 55,56 and 4 of them used color flow imaging. 36,[57][58][59]…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…In this study, the performance of the proposed CNN-assisted sparse array imaging was demonstrated on porcine teeth because of the value ultrasonography can have in oral health [ 25 27 ]. The porcine teeth were selected for three reasons: First, fresh porcine jaws could be easily obtained from a local abattoir.…”
Section: Introductionmentioning
confidence: 99%